(untitled) (LEARNing Landscapes, 2016)
What does it mean for artists within academia to make art, teach and learn with and in community, in particular the challenged and challenging Montreal neighborhood of Pointe-St-Charles? This article addresses community engagement in "The Point" from the perspectives of a doctoral student and two instructors involved in "The Right to the City" (TRTC), a three-year, interdisciplinary, placed-based teaching initiative of Concordia University (Montreal). Showcasing the student’s graphic novella, based on the oral history interview of a longtime resident, this article affirms the importance of reciprocity—learning with rather than about—within academic and artistic outreach.